Associations between hepcidin and immune response in individuals with hyperbilirubinaemia and severe malaria due to Plasmodium vivax infection. (December 2015) - Mendonça, Vitor; Souza, Ligia; Garcia, Gabriela; Magalhães, Belisa; Gonçalves, Marilda; Lacerda, Marcus; Barral-Netto, Manoel
Abstract Background Hyperbilirubinaemia (bilirubin >51.3 μmol/L) alone is not indicative of severe malaria, and the immune response underlying hyperbilirubinaemia remains largely unexplored. Liver damage associated with hyperbilirubinaemia may alter the expression of hepcidin, which regulates systemic iron by degrading ferroportin. For this study, the association between hepcidin and the levels of cytokines and chemokines in the serum of individuals with mild and severe vivax malaria and subjects with malaria with isolated hyperbilirubinaemia was evaluated. Methods Cytokines/chemokines and hepcidin were measured in individuals with mild (n = 72) and severe (n = 17) vivax malaria, as well as in the serum of subjects with vivax malaria with isolated hyperbilirubinaemia (n = 14) from the Brazilian Amazon between 2009 and 2013 by multiplex assay and ELISA, respectively. The polymorphism 744 G > T in theferroportin gene was identified by restriction fragment-length polymorphism analysis and the restriction enzymePvu II. Results The polymorphism at position 744 G > T in theferroportin gene was typed and no differences in the distributions of genotypes or alleles were observed between the study groups. Subjects with severe malaria had higher levels of interleukin (IL)-2 and IL-13 than subjects with hyperbilirubinaemia. No differences in the expression of immune markers were observed between subjects with mild malaria and those with hyperbilirubinaemia. However, hepcidin levels were higher in individuals with severe malaria and hyperbilirubinaemia than those with mild malaria (p = 0.0002 and p = 0.0004, respectively) and cut-off values of hepcidin differentiated these groups from subjects with mild malaria. Hepcidin was positively associated with IL-6 and IL-10 levels and with parasitaemia in subjects with mild malaria and with IFN-γ in subjects with severe malaria. Conclusions Malaria in the presence of hyperbilirubinaemia produces a less robust inflammatory response compared to severe cases of malaria. Hepcidin levels are positively associated with immune markers in vivax malaria outcomes.